2010
DOI: 10.1073/pnas.0912087107
|View full text |Cite
|
Sign up to set email alerts
|

Cell type specificity of chromatin organization mediated by CTCF and cohesin

Abstract: CTCF sites are abundant in the genomes of diverse species but their function is enigmatic. We used chromosome conformation capture to determine long-range interactions among CTCF/cohesin sites over 2 Mb on human chromosome 11 encompassing the β-globin locus and flanking olfactory receptor genes. Although CTCF occupies these sites in both erythroid K562 cells and fibroblast 293T cells, the long-range interaction frequencies among the sites are highly cell type specific, revealing a more densely clustered organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
215
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(237 citation statements)
references
References 40 publications
21
215
1
Order By: Relevance
“…A similar effect was observed in the mouse β-globin locus when CTCF binding sequences at 3′HS1 were mutated. Reduction of CTCF by shRNA or siRNA in K562 cells decreased the interaction frequency between HS5 and 3′HS1 of the human β-globin locus (Chien et al, 2011;Hou et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A similar effect was observed in the mouse β-globin locus when CTCF binding sequences at 3′HS1 were mutated. Reduction of CTCF by shRNA or siRNA in K562 cells decreased the interaction frequency between HS5 and 3′HS1 of the human β-globin locus (Chien et al, 2011;Hou et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…Recent data indicate that the cohesion complex interacts with CTCF and co-occupies CTCF sites in chromatin including at the β-globin locus (Hou et al, 2010;Wendt and Peters, 2009). This complex participates in chromatin loop formation in the β-globin locus.…”
Section: Introductionmentioning
confidence: 99%
“…First, CTCF and the cohesin complex, consisting of the core subunits SMC3, SMC1, RAD21, and STAG1/SA1 or STAG2/SA2, were found to colocalize extensively throughout mammalian genomes (3)(4)(5). Second, both factors are involved in mediating long-range interactions (6)(7)(8)(9)(10)(11). Finally, cohesin was shown to be important for CTCF's chromatin insulation function (3)(4)(5), whereas CTCF is necessary to recruit cohesin to the shared binding sites but not to chromatin (3).…”
mentioning
confidence: 99%
“…High-resolution chromatin conformation studies have revealed that cohesin forms long-range interactions between its binding sites (Figure 2) [13-18, [67][68][69][70]. Current models support the idea 6 that cohesin controls gene expression by contributing to the organisation of higher-order chromatin structure.…”
Section: Cohesin Shapes Interphase Chromatin By Forming Long-range Inmentioning
confidence: 94%
“…Current models support the idea 6 that cohesin controls gene expression by contributing to the organisation of higher-order chromatin structure. Communication between gene regulatory elements is believed to be a major mechanism for transcriptional control [71] and it is conceivable that interactions between cohesin binding sites that involve gene regulatory elements such as enhancers, promoters or insulators, would favour or inhibit gene expression [12][13][14][15][16][17][18][67][68][69]. These studies only survey a tiny proportion of the genome (Figure 2), and attempts to visualise cohesin effects on global chromatin organisation have to date been at low resolution.…”
mentioning
confidence: 99%